The ZIRP trap – The institutionalization of negative real interest rates - Bagus, Philipp (REVISTA PROCESOS DE MERCADO, 2015)
This paper analyzes the consequences of the monetary policies enact-ed by Western central banks from 2008 on and the possibilities to end these policies. Zero interest rate policies (ZIRP) actually impaired the recovery that was underway by subsidizing a distorted structure of production. The over indebtedness of Western economies was artificially propped up thus delaying recovery. We also show how ZIRP fosters moral hazard, the development of new bubbles and breeds unintended consequences that destabilize the finan cial system. ZIRP adversely influences entrepreneurship and culture by discour aging hard work and prudent investment. In today´s central bank world, ZIRP implies the institutionalization of negative real interest rates. It harms traditional entrepreneurial virtues, complicates long-term planning, politicizes society and erodes the foundations of capitalism. Exiting ZIRP is politically costly. We analyze the exit options that remain for policy makers, including financial repression, high inflation, default, capital levies, bail-ins and currency reforms, and evaluate them from a free-market perspective. Keywords: ZIRP, unconventional monetary policy, overindebtedness, exit op tions, negative real interest rates. JEL Classification: E14, E31, E32, E52 Resumen: Este artículo analiza las consecuencias de las políticas monetarias de los bancos centrales a partir de 2008 y la posibilidad de salir de estas políticas extraordinarias. ZIRP impidió la recuperación subvencionando una estructura productiva distorsionada. El sobreendeudamento de las economías occidentales se mantuvo y alargo artificialmente retrasando la recuperación. Mostramos también que ZIRP causa riesgo moral, el desarrollo de nuevas bur-bujas y consecuencias no intencionadas que desestabilizan el sistema financie-ro. ZIRP afecta negativamente a la función empresarial y a la cultura. Desincen-tiva el trabajo y la inversión prudente. En el mundo actual de bancos centrales, ZIRP implica la institucionalización de tipos de interés reales negativos. Daña las virtudes empresariales tradicionales, complica la planificación a largo pla-zo, politiza la sociedad y mina las bases del capitalismo. La salida de ZIRP es políticamente costosa. Analizamos las opciones de salida que les quedan a los políticos incluyendo la represión financiera, una inflación elevada, el incumplimiento en los pagos, los impuestos sobre el capital, bail-ins y reformas monetarias que son evaluadas desde una perspectiva liberal. Palabras clave: política de tipo de interés cero (ZIRP), política monetaria no convencional, sobreendeudamiento, opciones de salida, tipos de interés reales negativos. Clasificación JEL: E14, E31, E32, E52.